Anti-bacterial Activity of the Extract of Terminalia arjuna Against Multi Antibiotic Resistant Vibrio cholerae - Murad, F.; Alam, K. A.; Mazumdar, R. M.; Islam, S.; Nipa, M. N.; Iqbal, A.; Bhuiyan, H. R. (Journal of Scientific Research, 2010)
Morbidity and mortality due to diarrhoea continues to be a major problem in many developing countries. Water samples from different areas of Chittagong were collected and 22 Vibrio cholerae were isolated from the samples. In this experiment we found that 85% of the Vibrio cholerae isolated can grow at 6% NaCl whereas none of these can survive at 8% NaCl. Most of the isolates were resistant to at least 2 antibiotics. 95.45% were resistant to ampicillin, 50% to erythromycin, 63.63% to nalidixic acid, 13.63% to cephotaxine, 13.63% to ceftriaxone and 27.27% to cotrimoxazol. Arjun bark extract was used as a biological tool to resolve the antibiotic resistant V. cholerae problem. Arjun extract inhibited the growth of V. cholerae at all concentrations and zone diameter increased with the increase of concentrations. The regression coefficient of the relationship between concentration and zone diameter varies from 0.75 to 0.984 for most of the isolates which indicates that there exists a linear relationship. This study revealed that Terminalia arjuna would be a good antibacterial drug in the treatment of Vibrio cholerae infections, provided if found effective and nontoxic through in vivo studies. Keywords: Vibrio cholerae; Terminalia arjuna; Antimicrobial; Drug resistance. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.6094 J. Sci. Res. 3 (1), 129-137 (2011)